Sterilization of Money Inflows : Difficult (Calvo) or Easy (Reisen)? - Frankel, Jeffrey (IMF Working Papers; Working Paper ;, 1994)
Some countries undergoing exchange-rate-based stabilization and financial liberalization in Latin America, Asia and elsewhere have faced large capital inflows since 1991. Many have tried to sterilize the reserve inflows. Calvo, Leiderman, and Reinhart argue essentially that sterilization is more difficult than generally realized, due to the interest costs on sterilization bonds. Reisen argues essentially that sterilization is easier than generally believed. This paper reviews the issues in the simplest textbook model and concludes that local interest rates are not likely to rise if the source of the disturbance is an exogenous capital inflow, but will rise if the disturbance is an increase in money demand or an increase in exports.